Development and Implications of an Evidence-based and Public Health-relevant Definition of Complicated Appendicitis in Children. Issue 5 (May 2020) - Cameron, Danielle B.; Anandalwar, Seema P.; Graham, Dionne A.; Melvin, Patrice; Serres, Stephanie K.; Dunlap, Jonathan L.; Kashtan, Mark; Hall, Matthew; Saito, Jacqueline M.; Barnhart, Douglas C.; Kenney, Brian D.; Rangel, Shawn J.
Abstract : Objective: To characterize the influence of intraoperative findings on complications and resource utilization as a means to establish an evidence-based and public health-relevant definition for complicated appendicitis. Summary of Background Data: Consensus is lacking surrounding the definition of complicated appendicitis in children. Establishment of a consensus definition may have implications for standardizing the reporting of clinical research data and for refining reimbursement guidelines. Methods: This was a retrospective cohort study of patients ages 3 to 18 years who underwent appendectomy from January 1, 2013 to December 31, 2014 across 22 children's hospitals (n = 5002). Intraoperative findings and clinical data from the National Surgical Quality Improvement Program-Pediatric Appendectomy Pilot Database were merged with cost data from the Pediatric Health Information System Database. Multivariable regression was used to examine the influence of 4 intraoperative findings [visible hole (VH), diffuse fibrinopurulent exudate (DFE) extending outside the right lower quadrant (RLQ)/pelvis, abscess, and extra-luminal fecalith] on complication rates and resource utilization after controlling for patient and hospital-level characteristics. Results: At least 1 of the 4 intraoperative findings was reported in 26.6% (1333/5002) of all cases. Following adjustment, each of the 4 findings was independently associated with higher rates of adverse events compared with cases where the findings were absent (VH: OR 5.57 [95% CI 3.48–8.93], DFE: OR 4.65[95% CI 2.91–7.42], abscess: OR 8.96[95% CI 5.33–15.08], P < 0.0001, fecalith: OR 5.01[95% CI 2.02–12.43], P = 0.001), and higher rates of revisits (VH: OR 2.02 [95% CI 1.34–3.04], P = 0.001, DFE: OR 1.59[95% CI 1.07–2.37], P = 0.02, abscess: OR 2.04[95% CI 1.2–3.49], P = 0.01, fecalith: OR 2.31[95% CI 1.06–5.02], P = 0.04). Each of the 4 findings was also independently associated with increased resource utilization, including longer cumulative length of stay (VH: Rate ratio [RR] 3.15[95% CI 2.86–3.46], DFE: RR 3.06 [95% CI 2.83–3.13], abscess: RR 3.94 [95% CI 3.55–4.37], fecalith: RR 2.35 [95% CI 1.87–2.96], P  =  < 0.0001) and higher cumulative hospital cost (VH: RR 1.97[95% CI 1.64–2.37], P < 0.0001, DFE: RR 1.8[95% CI 1.55–2.08], P  =  < 0.0001, abscess: RR 2.02[95% CI 1.61–2.53], P < 0.0001, fecalith: RR 1.49[95% CI 0.98–2.28], P = 0.06) compared with cases where the findings were absent. Conclusion and Relevance: The presence of a visible hole, diffuse fibrinopurulent exudate, intra-abdominal abscess, and extraluminal fecalith were independently associated with markedly worse outcomes and higher cost in children with appendicitis. The results of this study provide an evidence-based and public health-relevant framework for defining complicated appendicitis in children.